2021
DOI: 10.1177/0021998320987897
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised graphene effect on the mechanical and thermal properties of recycled PA6/PA6,6 blends

Abstract: Limiting the generation of polymers waste and maximizing their recyclability and recovery have been the main focus of the research and industry in recent years. Recycling of polyamides leads to the loss in mechanical and thermal properties, therefore, in order to reuse recycled nylons, an enhancement in their properties is desired. Enhancing the properties of recycled polyamides by the addition of functionalised graphene nanoparticles (GNPs) was the goal of this study. Recycled PA6/PA6,6 blends and functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The tensile strength increased by 23.82% with the addition of fibers, and lower crystallinity was observed with the addition of NFC/MFC and CNC. Apart from cellulosic fillers, graphene has been previously added to the recycled nylon-6 matrix to enhance the tensile strength of the films at a lower concentration of 2 wt% [28]. In another study impact strength of recycled nylon-6 was improved by 55.5% with the addition of Hytrel (elastomer) [29].…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strength increased by 23.82% with the addition of fibers, and lower crystallinity was observed with the addition of NFC/MFC and CNC. Apart from cellulosic fillers, graphene has been previously added to the recycled nylon-6 matrix to enhance the tensile strength of the films at a lower concentration of 2 wt% [28]. In another study impact strength of recycled nylon-6 was improved by 55.5% with the addition of Hytrel (elastomer) [29].…”
Section: Introductionmentioning
confidence: 99%
“…25 Korkees et al studied recycled PA6/ PA6,6 blends-graphene nanocomposites; the results showed that the thermal conductivity of nanocomposites was improved using functionalised graphene. 26 As a result, it appears that combination of solution mixing and melt blending is the only way to achieve better graphene dispersion in polymeric materials with exceptional properties. 9 In this study, the delamination/adsorption method 18,27 is applied in which dimethylacetamide solvent is used to make novel carboxyl graphene/melamine-based polyamide (CGMPA) nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…25 Korkees et al studied recycled PA6/PA6,6 blends-graphene nanocomposites; the results showed that the thermal conductivity of nanocomposites was improved using functionalised graphene. 26 As a result, it appears that combination of solution mixing and melt blending is the only way to achieve better graphene dispersion in polymeric materials with exceptional properties. 9…”
Section: Introductionmentioning
confidence: 99%
“…10 They can be filled with graphene nanoparticles, glass fiber and talc to improve their properties or simply to reduce cost. [10][11]12 Studies regarding reprocessing of neat PA6, neat PA66, clay, talc and glass fiber filled polyamides have been carried out. Some authors [13][14][15] have investigated the effect of reprocessing on the mechanical properties of PA6 and observed a decrease in strain at break and impact strength and an increase in tensile strength and elastic modulus.…”
Section: Introductionmentioning
confidence: 99%